'More vital to our future than we realize?' Learning from Netting's thesis on smallholder farming, 25 years on. (December 2017) - Whitfield, Stephen
Twenty-five years on from Netting's paradigm challenging thesis about the dynamic efficiencies of household organization and the sophisticated nature of smallholder farming systems, the work continues to have relevance to contemporary debates about the future of smallholder agriculture in sub-Saharan Africa (SSA). This review is organized around four contemporary challenges for smallholder agriculture in SSA: (i) market centralization, liberalization and falling commodity prices; (ii) shifting agricultural research agendas and innovation funding; (iii) environmental degradation and climate change; and (iv) population pressures, large land acquisition and limited land availability. In each case, an argument inferred from Netting's thesis is presented alongside recent evidence, predominantly from research in SSA that supports and challenges it. Based on the lessons of Netting, in this contemporary context, it is argued that smallholder systems continue to have value and relevance and that rather than implementing protectionist strategies based on generic assumptions about smallholder vulnerability, that effort should be made to learn from the diversity of smallholder systems, knowledges and experiences of adapting to change.